The Effect of Rehabilitation Exercises and Electric Muscle Stimulation (X Body) on Optimizing Leg Connective Muscles Strength and Biomechanical variables for Injured Athletes - kassim Jawad, Wael; K. Mohammed, Luay; F. Atiyah, Wisam (International Journal of Psychosocial Rehabilitation, 2020)
This study is aiming to prepare therapy exercises to rehabilitate the injured hip joint connective muscles and treating exercises by Electric Muscle Stimulation (X Body) or EMS. Based on that, the leg biochemical variables need to be determined. An experimental method was used to discover the best solution for this case study. 10 injured athletes with connective muscle rupture (middle class injury) were selected. The samples were divided into two groups; the first group contained 5 athletes following a rehabilitation training program with EMS and the second group was also 5 athletes following a rehabilitation training program with no EMS. The variables studied are the maximal force of connective muscles (MFCM) measured by (kg), maximum power recorded (MPR) on power measurement platform by (Newton), angular velocity of the articular joint (AVAJ) and maximum height of the hip joint (MHHJ) by (cm). The apparatuses used for this purpose are a power measurement platform, video recording and a biomechanical analysis program (KINOVEA). Afterwards the data is processed by a SPSS-23 statistic program. The conclusion of this study confirmed that this type of training is gives a positive and efficient results when comparing between the two groups. There is a clear development in all measured variables by the use of (EMS) and therapy exercises.